Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Berkarir Sebagai Akuntan Pajak (Studi Pada Mahasiswa Prodi Akuntansi Universitas Negeri Di Pekanbaru) - Nelsi Arisandy; Putri Herlinda (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
This study aims to examine the effect of motivation, self efficacy, learning effectiveness of taxation courses and labor market considerations on the interest of accounting students to have a career as tax accountants. This study uses quantitative methods with primary data used in the form of questionnaires distributed to respondents and the results are analyzed using SPSS Version 23 as a test tool. The population in this study were students majoring in accounting, class 2018. The research sample amounted to 88 students, with the sample method used, namely the purposive sampling method. The data analysis method used is multiple linear regression analysis. The results showed that all independent variables, namely motivation, self efficacy, learning effectiveness of taxation courses and labor market considerations had a significant effect on the dependent variable, namely the interest of accounting students to have a career as tax accountants.